Hierarchical Self‐Assembly of Double‐Crystalline Poly(ferrocenyldimethylsilane)‐block‐poly(2‐iso‐propyl‐2‐oxazoline) (PFDMS‐b‐PiPrOx) Block Copolymers. Issue 18 (14th July 2015) - Rudolph, Tobias; Nunns, Adam; Stumpf, Steffi; Pietsch, Christian; Schacher, Felix H.
<x xml:space="preserve">Abstract</x> The step‐wise solution self‐assembly of double crystalline organometallic poly(ferrocenyldimethylsilane)‐block‐poly(2‐iso‐propyl‐2‐oxazoline) (PFDMS‐b‐PiPrOx) diblock copolymers is demonstrated. Two block copolymers are obtained by copper‐catalyzed azide‐alkyne cycloaddition (CuAAC), featuring PFDMS/PiPrOx weight fractions of 46/54 (PFDMS30‐b‐PiPrOx75) and 30/70 (PFDMS30‐b‐PiPrOx155). Nonsolvent induced crystallization of PFDMS in acetone leads in both cases to cylindrical micelles with a PFDMS core. Afterward, the structures are transferred into water for sequential temperature‐induced crystallization of the PiPrOx corona, leading to hierarchical double crystalline superstructures, which are investigated using scanning electron microscopy, wide angle X‐ray scattering, and differential scanning calorimetry.